2016
DOI: 10.1007/s13312-016-0894-0
|View full text |Cite
|
Sign up to set email alerts
|

Racecadotril in the management of rotavirus and non-rotavirus diarrhea in under-five children: Two randomized, double-blind, placebo-controlled trials

Abstract: Treatment with racecadotril did not reduce diarrheal duration, stool volume or the requirement for fluid replacement in children with acute gastroenteritis, both with and without rotavirus infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…In addition, one meta-analysis of seven clinical trials reported that racecadotril treatment is more effective than placebo or no intervention at reducing the duration of illness and stool output in children with acute diarrhoea 162 . However, in Kenya, racecadotril did not alter the number of stools after 48 hours, the duration of hospital stay or the duration of diarrhoea in children with severe gastroenteritis who received ORS and zinc 163 and was not effective in Indian children with acute diarrhoea and vomiting 164 . Thus, racecadotril can be considered for the management of children with severe secretory diarrhoea, but the efficacy is variable.…”
Section: Managementmentioning
confidence: 79%
“…In addition, one meta-analysis of seven clinical trials reported that racecadotril treatment is more effective than placebo or no intervention at reducing the duration of illness and stool output in children with acute diarrhoea 162 . However, in Kenya, racecadotril did not alter the number of stools after 48 hours, the duration of hospital stay or the duration of diarrhoea in children with severe gastroenteritis who received ORS and zinc 163 and was not effective in Indian children with acute diarrhoea and vomiting 164 . Thus, racecadotril can be considered for the management of children with severe secretory diarrhoea, but the efficacy is variable.…”
Section: Managementmentioning
confidence: 79%
“…Other, novel vaccines are currently undergoing preclinical and clinical trial testing[67], including vaccines using novel reassortant rotavirus strains, and vaccines using alternative delivery methods such as a heat stable oral formulation[69] and intramuscular or intradermal formulations[71]. Strategies to improve the performance of oral rotavirus vaccines in high-mortality countries are currently being explored, including the use of zinc supplementation[55], use of the antisecretory agent racecadotril[72,73], timing of breastfeeding[37,56,57], improved nutrition[35], and alternate dosing schedules[7476]. These developments in the rotavirus vaccine marketplace and improved effectiveness of oral vaccines are likely to encourage broader and more effective introduction of rotavirus vaccines in African countries, thus providing greater reductions in the burden of rotavirus infection than are estimated in this report.…”
Section: Five-year Viewmentioning
confidence: 99%
“…During study selection we encountered three non‐English articles and obtained help from the Cochrane Infectious Diseases Group (CIDG) with translating them into English (Calatayud 2009; Cojocaru 2002; García 2016). After selecting according to inclusion criteria, we included seven RCTs, involving 1140 participants (Cézard 2001; García 2016; Gharial 2017; [Kang 2016a; Kang 2016b]; Salazar‐Lindo 2000; Santos 2009; Sreenivas 2017). See Figure 1 for a flow diagram of the selection process.
Figure 1Study flow diagram.
…”
Section: Resultsmentioning
confidence: 99%
“…Two trials were conducted in India ([Kang 2016a; Kang 2016b]; Sreenivas 2017); the rest were conducted in France (Cézard 2001), Spain (Santos 2009), Peru (Salazar‐Lindo 2000), Kenya (Gharial 2017), and Ecuador (García 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation